(untitled) (Bangladesh Journal of Medical Science, 2024)
Objectives Fetal health locus of control has been indicated to effect how mothers approach their health beliefs and health-related decisions. The purpose of this study was to determine the fetal health locus of control (FHLC) level in high-risk pregnancies and to evaluate the factors affecting FHLC in high-risk pregnancies. Materials and methods The descriptive cross-sectional study was conducted with highrisk pregnant women. A total of 221 participants were included. Results and Discussion It was shown that The Internality Locus of Control was low and The Chance-Based Locus of Control was high in high-risk pregnant women. The current age of women and the age of their first pregnancy had a positively relationship with Powerful Others Locus of Control (FHLC-P). Although FHLC scores of multigravidas were higher than primiparous, no significant difference was found. Besides, there was a significantly higher FHLC-C score in women who did not change their exercise habits during pregnancy (p=0.008). Although the FHLC-I score was higher in women, who made changes in nutrition habits, it was determined that it was not significant. Conclusion The results of fetal health locus of control in high-risk pregnancies will lead to women who have high-risk pregnancies taking responsibility for adapting to the treatment process, taking into account the controls and making lifestyle changes, rather than leaving the situation to fate. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 438-446